2009
DOI: 10.1007/s10459-009-9202-2
|View full text |Cite
|
Sign up to set email alerts
|

Resident physicians’ perspectives on effective outpatient teaching: a qualitative study

Abstract: Learning theories, which suggest that experienced faculty use collaborative teaching styles, are reflected in qualitative studies of learners in hospital settings. However, little research has used resident focus groups to explore characteristics of successful teachers in outpatient clinics. Therefore, focus group discussions with first through third-year internal medicine residents at a large academic medical center were conducted to better understand residents' perspectives on effective outpatient teaching. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…However, the potential for this is minimal in this study, because the facilitator was trained beforehand and conducted the FGIs according to carefully considered guidelines. Second, the data for this study were obtained from written transcripts of the FGIs, which is less accurate than directly obtaining data from audiotapes [34]. Third, our comparisons with Sutkin’s categories may differ from the comparisons of others.…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential for this is minimal in this study, because the facilitator was trained beforehand and conducted the FGIs according to carefully considered guidelines. Second, the data for this study were obtained from written transcripts of the FGIs, which is less accurate than directly obtaining data from audiotapes [34]. Third, our comparisons with Sutkin’s categories may differ from the comparisons of others.…”
Section: Discussionmentioning
confidence: 99%
“…independently searched PubMed for English-language papers published since 2000 using different combinations of the following keywords: teaching, effectiveness, clinical, assessment, instrument, evaluation, teacher, and inventory. Through a literature search, six articles regarding attributes of effective teachers (one review of the literature article [6], five empirical studies [3, 4346]), and seven articles of instruments to evaluate clinical teachers (all empirical studies) [4, 11, 12, 14, 15, 47, 48] were identified. All of the articles were reports from Western countries except Zuberi’s Instrument (SETOC) from Pakistan.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical teaching is essential when residents are trained in clinical practice [2, 3] and is recognised as an important aspect in the postgraduate educational environment [4]. By acting as role models and providing support, clinical teachers can optimize the learning potential of the workplace [5].…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to what we had found in previous qualitative studies at our institution, which showed that narrative comments provide, more than quantitative questionnaire data, valuable information regarding interpersonal dynamics. 30 Finally, faculty members' satisfaction and improved confidence with group assessment were surveyed with a non-validated instrument (so information regarding the properties of this instrument are unknown) and were not substantiated by objective measures. Future studies should assess whether these perceptions can be confirmed objectively.…”
Section: Discussionmentioning
confidence: 99%